Ultrasonic Spray Drying Vs High Vacuum and Microwaves Technology for Blueberries - Gaete-Garreton, L; Vargas-Hernandez, y; Candia-Munoz, N (Elsevier, 2015)
Interest in high quality foods: good taste and a high content of nutrients with healthy beneficial effects are increasing. Fruits have good properties but, they are lost because the oxidation process, additionally, for different reasons a 40% of harvested fruit are lost. To conserve the fruit properties an ultrasonic assisted spray dryer was developed and tested, comparing its results with microwave-vacuum drying technology. Results did shown taste, color, smell, particle shape and size distribution better than the conventional one. The antioxidants conservation were quite good except in the anthocyanins, in which the microwave and vacuum technology shown best results. © 2015 The Authors.